Mixed‐layer carbon cycling at the Kuroshio Extension Observatory. Issue 2 (4th February 2017) - Fassbender, Andrea J.; Sabine, Christopher L.; Cronin, Meghan F.; Sutton, Adrienne J.
Abstract: Seven years of data from the NOAA Kuroshio Extension Observatory (KEO) surface mooring, located in the North Pacific Ocean carbon sink region, were used to evaluate drivers of mixed‐layer carbon cycling. A time‐dependent mass balance approach relying on two carbon tracers was used to diagnostically evaluate how surface ocean processes influence mixed‐layer carbon concentrations over the annual cycle. Results indicate that the annual physical carbon input is predominantly balanced by biological carbon uptake during the intense spring bloom. Net annual gas exchange that adds carbon to the mixed layer and the opposing influence of net precipitation that dilutes carbon concentrations make up smaller contributions to the annual mixed‐layer carbon budget. Decomposing the biological term into annual net community production (aNCP) and calcium carbonate production (aCaCO3 ) yields 7 ± 3 mol C m −2 yr −1 aNCP and 0.5 ± 0.3 mol C m −2 yr −1 aCaCO3, giving an annually integrated particulate inorganic carbon to particulate organic carbon production ratio of 0.07 ± 0.05, as a lower limit. Although we find that vertical physical processes dominate carbon input to the mixed layer at KEO, it remains unclear how horizontal features, such as eddies, influence carbon production and export by altering nutrient supply as well as the depth of winter ventilation. Further research evaluating linkages between Kuroshio Extension jet instabilities, eddy activity, and nutrient supply mechanisms is needed to adequately characterize the drivers and sensitivities of carbon cycling near KEO. Key Points: Annual net community production and calcium carbonate production in the mixed layer is 7 ± 3 and 0.5 ± 0.3 mol C m −2 yr −1, respectively KEO exhibits an intense spring bloom period with an annual mean PIC:POC production ratio of 0.07 ± 0.05 Research linking nutrient supply mechanisms and Kuroshio Extension jet stability to annual carbon export is needed